The Politics of Tourism Development - O'Brien, A. author. aut Link
VIII, 213 p.
Keywords: Moving beyond both tourism and politics literatures' current understandings of how tourism is developed, this book offers an original theory of interlocking regimes to account for the manner in which public and private bodies either facilitate or prevent development within tourism.